Unraveling Migraine: Innovative Approaches to Understanding and Managing a Debilitating Disorder (Homoeopathy for All, 2024)
Migraine is a prevalent and disabling neurological disorder characterized by recurrent episodes of moderate to severe headache, typically accompanied by associated symptoms such as nausea, vomiting, and heightened sensitivity to light and sound. Affecting approximately 12% of the global popu la tio n, migraine presents a significant burden not only to individuals but also to healthcare systems and society at large due to its impact on quality of life and productivity.
Keywords: pharmacological; management strategies.; CLASSIFICATION